Penentuan Calon Kepala Depo Pada PT Lancaster Nusantara Cigarindo Menggunakan Metode SAW - Wulandari, Ika Arthalia; Siregar, Guna Yanti Kemala Sari (Jurnal Komtika (Komputasi dan Informatika), 2020)
As a quality and service improvement process, the management has thought and decided to establish a new branch in Metro City. Determining the Head of Depo is an absolute necessity for a branch office to open. The importance of the duties of the Head of Depo (Kadepo) means that the management from the head office must precisely determine the Kadepo candidates to lead the branch office candidates. The decision support system for determining Depo Head candidates has the objective of selecting the Depo Head from several Depo Head candidates who have been nominated by utilizing this decision support system using the Simple Additive Weighting (SAW) method. This study aims to help PT. Lancaster Nusantara Cigarindo in making decisions on the results of Candidates for Head of Depo. The five specified data for Depo Head Candidates found that the Chosen Candidate with code CK1 was the best Depo Head candidate. This proves that the SAW method can be used to determine the Candidates for the Head of Depot in a company.